(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
Vocabulary plays a crucial role in communication and language development. It is one of the fundamental components of language proficiency, enabling individuals to express ideas, emotions, and information effectively. Without sufficient vocabulary, communication becomes limited and unclear. This article discusses the importance of vocabulary in communication, its impact on speaking, listening, reading, and writing skills, and strategies for vocabulary development. The paper also highlights the role of teachers and modern technologies in improving learners’ vocabulary competence. The study concludes that strong vocabulary knowledge improves communication ability and increases learners’ confidence in using English.